Development of VLAB-CHEM for Chemistry subject based on Constructivism-Cognitivism-Contextual approach - Bakar, Norasiken; Badioze Zaman, Halimah (School of Electrical Engineering and Informatics, Institue Teknologi Bandung, 2007)
This paper is about development of virtual laboratory for chemistry subject (VLab-Chem). In this research, the term virtual laboratory is used to show the student that there are in a real laboratory when they done their experiment using computer. Student can interact with the material and apparatus, and also see the reaction in the experiment fully with animation and simulation. Discussion involved in the theoritical framework modelling where it divided into two parts that is analysis, design , development and evaluation. For the second objective, researchers also explained the laboratory architecure of development VLab-Chem. While designing the development of VLab-Chem, researcher has used approach in learning theory such as constructivism-cognitivism-contextual. Concept through learning-by-doing, contextual education, simulation, animation to create virtual based on learning, added in the VLab-Chem.